The Optimal Approach for Kolmogorov-Smirnov Test Calculation in High Dimensional Space - Akopov, Norayr Z.; Martirosyan, Narek H. (Mathematical Problems of Computer Science, 2021)
Numerical estimation of the Kolmogorov-Smirnov discrepancy DN in high dimensional space is an extremely time and memory consuming problem. New approach with the minimal bin number, which essentially reduces the time and memory requirements, to perform the DN tests in two and more dimensional space is discussed.